Evaluation of Sterculia foetida L. gum as natural based disintegrating excipient - Quan, Vu Thi Hong; Quan, Nguyen Thi; Phong, Mai Thanh; Phung, Le Thi Kim (Vietnam Journal of Science and Technology, 2019)
Therefore, the physicochemical properties of Sterculia foetida L. gum, including solubility, scanning electron micrographs, melting point, swelling index, pH, viscosity, loss on drying were determined. Furthermore, compressed tablets were successfully prepared for in vitro studies at many different particle sizes, concentrations of gum, rotational speeds and media in order to evaluate the effects of these parameters on the rate of drug release. Besides, SFG tablets were compared with the tablets prepared with Hydroxymethylcellulose E15. The findings indicated that Sterculia foetida L. gum exhibited an excellent potential in managed release dosage forms.